1992
DOI: 10.1128/aem.58.3.884-890.1992
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced control of Listeria monocytogenes by in situ-produced pediocin during dry fermented sausage production

Abstract: To determine whether pediocin is produced and has effective antilisterial activity during food fermentation, six sausage fermentation trials were conducted with antibiotic-resistant, pediocin-producing (Bac+) Pediococcus acidilactici PAC 1.0 (Strr RiF) and an isogenic pediocin-negative (Bac-) derivative used as a control. Meat was inoculated (ca. 105 CFU/g) with a composite of five Listeria monocytogenes strains, each electrotransformed with pGK12 (Cmr Emr). P. acidilactici and L. monocytogenes populations wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
0
10

Year Published

1993
1993
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(80 citation statements)
references
References 23 publications
(29 reference statements)
4
65
0
10
Order By: Relevance
“…monocytogenes [14,148,156,157], general interest has flourished towards the application of pcdiocin-producing starters in fermented meat products. Numerous studies have now evaluated the efficacy of pediocin PA-I/AcH in various food systems with promising results [153,156,[158][159][160][161]. The bactericidal action of pediocin PA-I/AcH and JD occurs at the cytoplasmic membrane to cause a collapse of the pH gradient and proton motive force [150,162].…”
Section: Pediocin Pa-i /Achmentioning
confidence: 99%
“…monocytogenes [14,148,156,157], general interest has flourished towards the application of pcdiocin-producing starters in fermented meat products. Numerous studies have now evaluated the efficacy of pediocin PA-I/AcH in various food systems with promising results [153,156,[158][159][160][161]. The bactericidal action of pediocin PA-I/AcH and JD occurs at the cytoplasmic membrane to cause a collapse of the pH gradient and proton motive force [150,162].…”
Section: Pediocin Pa-i /Achmentioning
confidence: 99%
“…Listeria monocytogenes L182 and L830, isolated from vacuumpackaged sliced meat and chicken marinade, respectively, were adapted to rifampicin (Foegeding et al 1992). Control experiments revealed that rifampicin-resistant (rif R ) cells grew as did rifampicin-sensitive (rif S ) cells at 4 and 10°C in Brain Heart Infusion broth (BHI) without added rifampicin.…”
Section: Bacterial Strains and Preparation Of Inoculamentioning
confidence: 99%
“…It is important, at this point, to avoid contamination and the use of LAB/bacteriocins has been suggested to minimize the risk of outgrowth of L. monocytogenes (Stiles 1996;Bredholt et al 2001;Goff et al 1996). Several bacteriocinogenic cultures have been successfully used as a hurdle for L. monocytogenes (Foegeding et al 1992;Winkowski et al 1993;Hugas 1998;Duffes et al 1999). Lactobacillus sakei inhibits the growth of L. monocytogenes on cold smoked salmon and has been shown to produce bacteriocin when growing on this product (Katla et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Another approach could be the use of starter or protective cultures producing antilisterial bacteriocins active against nisin-resistant cells of L. monocytogenes. Numerous studies have shown that bacteriocin-producing lactic acid bacteria are able to suppress growth of L. monocytogenes in meat and other foods (Schillinger et al 1991;Foegeding et al 1992;Degnan et al 1992;Maisnier-Patin et al 1992;Winkowski et al 1993;Stiles 1996). There are, however, no studies on the effectiveness of bacteriocinogenic cultures towards nisinresistant mutants of L. monocytogenes.…”
Section: Introductionmentioning
confidence: 99%